The Use of the Goldfinger Dissector (GD) in Laparoscopic Sacrocolpopexy - Talla, Pascal; Ekotomati, Maria; O'Leary, Tara; Ben Ali, Nordine (Frontiers in Medicine, 2018)
We tested the employment of the GD to create a retroperitoneal tunnel between the promontory and the vaginal apex during the laparoscopic sacrocolpopexy with a mesh. Thus far no report has experimente the use of the GD in this indication. This study’s aim was to evaluate the safety and the interest to use this laparoscopic instrument. 16 consecutive patients underwent a laparoscopic sacrocolpopexy with the use of the GD and were compared with a control group constituted by the previous 30 cases. The median operating time was 180 minutes with the use of the GD and represent a gain of time of 22 minutes in comparaison with our control group. No conversion to open or complications were recorded. In our limited experience, the use of the GD allows a significant gain of time and limits the amount of peritoneal dissection.